The impact of a head and neck microvascular fellowship program on otolaryngology resident training. (11th June 2017) - Zender, Chad A.; Clancy, Kate; Melki, Sami; Li, Shawn; Fowler, Nicole
Abstract : Objective: To assess the impact of a microvascular head and neck (H&N) fellowship on senior residents' surgical experience. Study Design: Retrospective review of Accreditation Council for Graduate Medical Education‐generated operative case log reports, retrospective chart review, and electronic survey. Methods: A retrospective review of one institution's residents' H&N operative case logs and free flap operative reports was performed to determine changes in key indicator cases (KICs) after the addition of a H&N fellowship. An electronic survey was distributed to senior residents at all U.S. otolaryngology residency programs to determine residents' perceptions of a H&N fellow's impact on their surgical experience. An electronic survey was distributed to senior medical students applying to surgical residencies to explore the perceived impact that a fellowship has on the desirability of a residency program. Results: The average number of each postgraduate year (PGY)5's H&N KIC before and after the addition of the fellowship were: parotidectomy, 19 versus 17.8; neck dissection, 33.2 versus 40.6; oral cavity resection, 15.3 versus 12.6; thyroid/parathyroid, 45.5 versus 45.6; and flaps/grafts, 56.7 versus 42. PGY5 participation as first assistant in free flaps dropped from 78% to 17%; however, residents still participated in some aspect of 45% of the cases. Seventy percent of senior residents reported a positive perception of the H&N fellow on their H&N operative experience. Eighty‐nine percent of senior medical student respondents reported a nonnegative perception of a fellowship in their applied field. Conclusion: The addition of a H&N fellowship did not decrease senior residents' H&N KIC, and most senior residents at programs with fellowships report that the fellow has a positive impact on their H&N operative experience. Level of Evidence: 4. Laryngoscope, 128:52–56, 2018